Encryption and Compression Digital Video Files using Artificial Neural Networks and Genetic Algorithm - Hasan Anwer (College of Education for Pure Sciences, 2019)
The research and studies of encryption and compression of digital files to the confidentiality and ease of dealing with networks and the Internet, by reducing the size of files transmitted through multimedia, and also used to increase the confidentiality of information transmitted. The purpose of the research is to encrypt and compress colored digital video files using artificial neural networks and genetic algorithm, The digital video file is entered into Audio Video Interleave (AVI) and cut into a set of frames, Each frame is then analyzed into the three color segments (red, green and blue) And an audio input from the Waveform Audio File Format  (WAV) type (which represents the encryption key), the encoded frame was then inserted into the compression algorithm, A hybrid compression method was adopted which is considered as one of the solutions that reduces the size of the required data on the one hand and gives it a secret on the other, Where it was segmentation and clustering the encoded frames into a cluster of clusters (The optical pixels), which have been introduced into the artificial neural network (back propagation network), The genetic algorithm has been used to calculate the weight values ​​of each cell of the network. The decryption and decompression is then performed, and by using a set of testing and comparison tools that showed that the results were consistent with the research requirements, and Matlab R2017b was used to implement research algorithms.